2024 bibliometric toolkit: how to use Scopus, Biblioshiny & VOSviewer - Abd. Rahim, Nour El Huda; Mat Rashid, Siti Norain; Azman, Norainin Sofiya (Malaysian Integrated Medical Professionals Association (MIMPA), 2024)
The module originates from the insights and materials presented during a Bibliometric Analysis Workshop conducted on the 24th of February and the 5th of March, 2024, at the Department of Pathology and Laboratory Medicine Sultan Ahmad Shah Medical Centre @IIUM. The main objective of this module is to provide researchers with a comprehensive guide on how to effectively navigate and analyse scientific literature across different disciplines using bibliometric tools such as Scopus, Biblioshiny and VOSviewer. The guide also introduces the idea of a “Journal Bank” to assist researchers in preparing and submitting their manuscripts for publication.